The effect of silver addition on microstructure and thermal properties of the Cu-10%Al-8%Mn shape memory alloy - Manasijevic, Dragan Miroslav; Balanović, Ljubiša; Holjevac Grgurić, Tamara; Stamenković, Uroš; Minić, Duško; Premović, Milena; Todorović, Radiša; Å trbac, Nada; Gorgievski, Milan; Gojić, Mirko; Govorčin Bajsić, Emi (Metallurgical and Materials Engineering, 2017)
The influence of Ag addition on microstructure and thermal properties of the Cu-10%Al-8%Mn alloy was investigated in this work. Two alloys with designed compositions Cu-10%Al-8%Mn and Cu-10%Al-8%Mn-4%Ag (in wt.%) were prepared by induction melting of pure metals. Microstructures of the prepared samples were investigated in the as-cast state, after homogenization annealing and after quenching. The effects of different methods of heat treatment on the microstructure and transformation temperatures of the investigated Cu-10%Al-8%Mn and Cu-10%Al-8%Mn-4%Ag alloys were investigated using SEM-EDS and DSC techniques. It was determined that after induction melting microstructure of the both investigated alloys are primarily composed of martensite and a small amount of α-phase precipitates. Fully martensitic structure in both investigated alloys was obtained after direct quenching from the 850 °C into the ice water. Based on the DSC cooling curves it was determined that two-step martensite transformation for the both investigated alloys occur in the temperature interval from about 30 to -40 °C.